The multiple manifestations of the “factory shop” phenomenon: A research-based evaluation of supply and demand in Metzingen from a spatial planning perspective - Halder, Gerhard; Schenk, Winfried (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
The current debate on the spatial effects of factory shops has focused predominantly on factory outlet centres (FOCs) as the channel of supply. This orientation tends to ignore the long history of factory shops in some parts of Germany, a tradition which lies behind the broad range of shopping facilities of this type available today. This heterogeneity is clearly revealed in the studies on supply and demand at two representative outlets: thesBoss andSamtfabrikshops at the “Mecca of factory shops” situated in Metzingen, near Reutlingen (Baden-Württemberg). In addition to forms of supply which are of questionable value to regional economies, there are — as these studies show — also other types of outlet which appear to be less problematic from the spatial planning perspective. Outlets of the latter type offer high-quality products and pull purchasing power into the region. As these outlets are themselves homegrown within the region, the retail sector in the region has been able to adapt to face the challenge they pose. Businesses of this type may even provide a boost for city-centre development if they are located relatively close to city centres.